Política regional na Uni\~ao Européia: Transformaç\~oes recentes e recomendaç\~oes para o caso brasileiro - José Raimundo de Oliveira Vergolino (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The main objective of this paper is to compare the European Union's (EU) Regional Policy with the Regional Policy in Brazil. In this context, the transformations that have occurred in the last two decades in the policies and instruments that promote the economic and social development of the countries that form the EU are discussed. The experience of EU Regional Policy can, in many ways, emulate Brazilian researchers and national and sub-national governments, to design and implement good public policies to address regional inequalities. The National Policy for Regional Development (PNDR), under the responsibility of the federal government, showed substantial advances in the period 2007-2020. However, the National Fund for Regional Development (FNDR), the main vector of structural changes and which would provide financial support for the creation of Policies and Programs at the national level, was not created. The absence of such an instrument represents a major constraint on the greater effectiveness of the PNDR to the process of minimizing regional inequalities in Brazil.
Keywords: O2; R5; R58; 330; regional development; regional policy; economic development; European Union